Slip Effect Study of 4:1 Contraction Flow with Rounded Corner Geometry for Newtonian Fluid - Thongjub, Nawalax; Ngamaramvaranggul, Vimolrat; Puangkird, Bumroong (Science & Technology Asia, 2015)
The simulation of slip effect for 4:1 contraction problem with rounded corner geometry for Newtonian fluid is determined to study kinematic behaviors from streamline path, shear stress values and vortex size by a model of Navier-Stokes equation. Two-dimensional planar isothermal incompressible creeping flow with slip and no slip condition is considered with a semi-implicit Taylor-Galerkin pressure-correction based on the finite element method. The streamline-Upwind/Petrov-Galerkin and velocity gradient recovery schemes are employed to stabilize the converged solution. The slip velocity is computed after each time step and the modification of slip coefficient is adjusted to proper slip velocity in order to reduce the vortex size and stress along the channel wall. Finally, the best mesh is selected to run for the final solution and the slip condition of Phan-Thien slip rule on the channel wall is done to get the result to be in better agreement with experiment.